Monoamine Oxidase A Contributes to Serotonin - But Not Norepinephrine-Dependent Damage of Rat Ventricular Myocytes - Knittel, Jonas; Itani, Nadja; Schreckenberg, Rolf; Heger, Jacqueline; Rohrbach, Susanne; Schulz, Rainer; Schlüter, Klaus-Dieter; Justus Liebig University Giessen (My University, 2023)
Serotonin effects on cardiac hypertrophy, senescence, and failure are dependent either on activation of specific receptors or serotonin uptake and serotonin degradation by monoamine oxidases (MAOs). Receptor-dependent effects are specific for serotonin, but MAO-dependent effects are nonspecific as MAOs also metabolize other substrates such as catecholamines. Our study evaluates the role of MAO-A in serotonin- and norepinephrine-dependent cell damage. Experiments were performed in vivo to study the regulation of MAOA and MAOB expression and in vitro on isolated cultured adult rat ventricular cardiomyocytes (cultured for 24 h) to study the function of MAO-A. MAOA but not MAOB expression increased in maladaptive hypertrophic stages. Serotonin and norepinephrine induced morphologic cell damage (loss of rod-shaped cell structure). However, MAO-A inhibition suppressed serotonin-dependent but not norepinephrine-dependent damages. Serotonin but not norepinephrine caused a reduction in cell shortening in nondamaged cells. Serotonin induced mitochondria-dependent oxidative stress. In vivo, MAOA was induced during aging and hypertension but the expression of the corresponding serotonin uptake receptor (SLC6A4) was reduced and enzymes that reduce either oxidative stress (CAT) or accumulation of 5-hydroxyindolacetaldehyde (ALDH2) were induced. In summary, the data show that MAO-A potentially affects cardiomyocytes’ function but that serotonin is not necessarily the native substrate.
Keywords: oxidative stress; mitochondria; ageing; ddc:610